How many 24-hour recalls or food records are required to estimate usual energy and nutrient intake? - Rosângela Alves Pereira; Marina Campos Araujo; Taís de Souza Lopes; Edna Massae Yokoo
For dietary intake assessments, one needs to know the minimum 24-hour recall or food record replications that are required to estimate usual energy and nutrient intake and to classify subjects correctly according to their nutrient intake. Data from two different studies on dietary intake that were carried out with 300 adults and 169 adolescents in the Rio de Janeiro Metropolitan area, Brazil, were analyzed. To estimate the number of replications two methods were applied: one based on the variances ratio, the other based on the within-subject variance alone. The most important results found were the requirement for 14 replications for boys and men, 15 for girls, and 23 for women in order to estimate energy intake with a precision of 90%. Also four replications for boys and seven for men, girls and women are required to classify individuals' energy intake with a correlation coefficient of 0.9. Due to the within variance in food intake, a larger number of replications is required to obtain estimates of usual intakes than is needed to classify subjects according to levels of dietary intake.